Freshwater bivalves as reservoirs of multiresistant bacteria: the case of two endangered species (Margaritifera margaritifera and Potomida littoralis) - Varandas, Simone (2021)
Freshwater bivalves (FB), responsible for important functions and vital ecosystem services are sensitive to environmental changes, making them excellent bioindicators